Pengaruh Spasi dan Panjang pada Kelompok Tiang Terbuka di Pasir: Studi Model Kelompok Tiang dan Fondasi Blok - Agus Nugroho, Soewignjo; Satibi, Syawal; Putra, Andius Dasa; Andriani, Andriani (Journal of Infrastructure and Construction Technology, 2023)
Planning for existing construction requires taking into consideration the exact location of the structure; sandy soil is typically found in Indonesia, and pile foundations are a very frequently used type of support. Whenever the stable soil is located at a quite deep depth or when the building's foundation is situated on a relatively high embankment, the pile foundation is utilized to support the structure. Given the quantity of pile foundations utilized in Riau, where soft soil makes up the majority of the soil type, a study on pile foundations is necessary. A possible research approach involves conducting a small-scale pile foundation modeling experiment to determine the group pile's bearing capacity on sand soil, taking into account variations in the pile's length and space. Direct testing on a pile foundation model with length, spacing, and length variations of 20, 30, and 40 cm as well as spacing variations of 2.5D, D, and 5D was used for the research. Pile group length 40 cm has the highest capacity, according to the results of a direct loading test conducted with a spacing of 2.5D. According to the findings of the Terzaghi and Peck method interpretation, the pile with a length of 40cm and 2.5D spaces has the largest qult of 1.665 kN. A pile with a length of 40cm and 2.5D pile spacing is the pile with the largest qult of 2.232 kN, followed by a pile with a length of 30cm and a space of 2.5D. Based on the results of the investigation, it can be stated that Qult will get higher the more closely spaced the pile exists and that Qult will become higher the longer the pile is on the foundation model.